Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.22159/ajpcr.2019.v12i9.34382
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Traditional Medicinal Plants Used in the Management of Diabetes in the Urban Areas of Khurda, Odisha, India

Abstract: Objective: The present work deals in collecting information about the medicinal plant species used for the treatment of diabetes by the traditional healers in the urban areas of Khurda districts of Odisha and identification as well as documentation of these species. Methods: Extensive field survey was conducted in the study area; information about plants were collected from local herbal practitioners, village elders, patients, and traditional healers through normal conversations, interviews, and discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that a number of them are efficacious in the management of diabetes. [ 78 ] Inhibiting the α‐glucosidase enzyme in the digestive tract is one of the most effective strategies for maintaining postprandial glucose levels by slowing down glucose absorption. [ 79 ] Antidiabetic medicines now utilized in clinical practice are successful in lowering sugar levels in type‐2 diabetic patients.…”
Section: Future Perspectivementioning
confidence: 99%
“…Numerous studies have demonstrated that a number of them are efficacious in the management of diabetes. [ 78 ] Inhibiting the α‐glucosidase enzyme in the digestive tract is one of the most effective strategies for maintaining postprandial glucose levels by slowing down glucose absorption. [ 79 ] Antidiabetic medicines now utilized in clinical practice are successful in lowering sugar levels in type‐2 diabetic patients.…”
Section: Future Perspectivementioning
confidence: 99%